A Physics-Informed, Data-Driven Framework for Spatially Resolved Motion Sickness Prediction on The SA Agulhas II - Melim, Micaela Do Amaral (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.